Halloween animatronics : build a zombie crawler - Donat, Wolfram (Great Britain : Amazon, 2014)
Halloween Animatronics: Build a Zombie Crawler is a guide to building your own creepy zombie to chase your friends and scare the neighborhood children. Amply illustrated, and including a full parts list, the author takes you step by step through the process of building a fully functional radio-controlled zombie crawler named Bartok, all for a reasonable price. You'll see how to build his body, from his arms to his rib cage, and how to connect his arms to his shoulder motors to make him crawl on command. Also includes a primer on RC tech, for those new to the hobby, and a troubleshooting section. Packed with information, this is a Halloween prop how-to that any serious Halloween fanatic can't miss!
Keywords: Robotics; Halloween decorations